The housing market and housing policies in Japan - Masahiro Kobayashi (Asian Development Bank Institute (ADBI), 2016)
Housing policies in Japan after World War II were focused on the quantitative supply of houses with a wide range of targeted groups and public rental houses. The Japan Housing Corporation (now the Urban Renaissance Agency) and the Government Housing Loan Corporation (now the Japan Housing Finance Agency) have served to address these policy targets accordingly. The restoration of housing stock was successful, but the collapse of the property bubble in the early 1990s caused negative impact on the real economy and created persistent loss of confidence among the Japanese people, which is exacerbated by deflation and negative demographic factors (decrease of the population and aging of society). Enhancement of the quality of houses is an important part of the housing policy in Japan, but, at the same time, there needs to be a balance between new construction and the activation of existing housing stocks. Given the social experiments currently underway, there is need to closely monitor the changes of market trends.
Keywords: R14; R21; R31; R38; 330; Japan housing policy; housing stock; property bubble; Japan Housing Finance Agency